Intratumoral STING activations overcome negative impact of cisplatin on antitumor immunity by inflaming tumor microenvironment in squamous cell carcinoma - Harabuchi, Shohei; Kosaka, Akemi; Yajima, Yuki; Nagata, Marino; Hayashi, Ryusuke; Kumai, Takumi; Ohara, Kenzo; Nagato, Toshihiro; Oikawa, Kensuke; Ohara, Mizuho; Harabuchi, Yasuaki; Ohkuri, Takayuki; et al. (Biochemical and biophysical research communications, 2020)
Although cisplatin (CDDP) has been used as a major chemotherapeutic drug for head and neck squamous cell carcinoma (HNSCC), its impact on T-cell functions is controversial. Therefore, we investigated the immunologic effects of CDDP and antitumor effects by combination therapy of CDDP with a ligand for stimulator of interferon genes, cyclic guanosine monophosphate-adenosine monophosphate (cGAMP). Direct impacts of CDDP on T-cell functions were addressed by comparing T-cell functions between human subjects treated and untreated with CDDP. The immune responses and the efficacy of combination therapy using CDDP and cGAMP were assessed using BALB/c mice inoculated with mouse squamous cell carcinoma (SCC) cell lines. CDDP inhibited T-cell proliferation in a dose-dependent manner. T-cell functions of CDDP-treated HNSCC patients were comparable to those of healthy donors and CDDP-untreated HNSCC patients. In the mice bearing SCC cell lines, combination therapy using CDDP and cGAMP enhanced the gene expressions of CXCL9 and CXCL10 in the tumor tissues and inhibited tumor growth. The antitumor effect was cancelled by anti-CXCR3 monoclonal antibody. These findings suggest that the combination therapy using CDDP and an immunomodulating drug like cGAMP would be a rational cancer immunotherapy for patients with HNSCC. •T-cell functions of the patients treated with cisplatin are comparable to those of the healthy donors.•Intratumoral administration of cGAMP upregulates gene expressions of CXCL9 and CXCL10 in the tumor site.•Combination of CDDP and cGAMP shows antitumor effect in mice bearing squamous cell carcinoma.